THE VALUE ORIENTATION OF TEACHERS OF PRIMARY AND SECONDARY GRAMMAR SCHOOLS - Sandor, ALBERT (Trends in education, 2008)
This article reflects the value orientation of Slovakian teachers of primary and secondary grammar schools. Within the frame of an appraisal we present, in what kind of school would our practicing teachers work in.
Keywords: vision; mission; school-program; values; value orientation; examination